Effect of Basic Movement Skills in The Game of Ability Early Children's Cognitive - Haris HDP; Agung Sunarno; Albadi Sinulingga (Universitas Negeri Medan, 2020)
In line with the theories which write that motion can help improve cognitive abilities, the golden age of formation is at the age of 5-6 years. The sample taken was early childhood education, with the aim of the study was to see the influence of basic movement skills on cognitive abilities. The research method uses experiment. Basic movement skills become a stimulant to help improve basic movement skills. With a sample size of 28 people who were divided into 2 groups, it was found that children with high basic motor skills were in line with children's cognitive abilities. Based on the results of the study, it is hoped that the kindergarten / early childhood education level units will make movement skills the focus that is applied to the curriculum.